Green product purchase intention: impact of green brands, attitude, and knowledge. - Norazah Mohd Suki (Emerald Group Publishing Limited, 2016)
Purpose: The purpose of this paper is threefold: to assess the impact of green brand positioning, consumers’ attitude toward green brands, and green brand knowledge on green product purchase intention; to investigate the influence of green brand knowledge on consumers’ attitude toward green brands; and to examine the moderating effect of green brand knowledge on the relationship between green brand positioning and green product purchase intention. Design/methodology/approach: A questionnaire was utilized to gather the data (n=300) for this study. The purposive sampling technique was used, involving respondents who practice a green lifestyle and have had green product purchasing experience. The partial least squares (PLS) method, which is a variance-based technique for the analysis of structural equation modeling, was used to analyze the data, with the assistance of the SmartPLS computer program version 2.0. Findings: Based on the standardized path coefficients of the structural model from the PLS results, green brand knowledge was found to be the most significant determinant of green product purchase intention. Knowledge of green brands has caused consumers to develop positive green marketing awareness and has bolstered their interest in fortifying the environment whilst preventing its degradation. Furthermore, green brand knowledge also impacted consumers’ attitude toward green brands. However, this factor was an insignificant moderator of the impact between green brand positioning and green product purchase intention. Practical implications: Green brand positioning can be used by firms and businesses to better market their products and improve consumers’ green brand knowledge and attitude toward green brands, as well as increase green brand purchase intentions. Successful green brand positioning is seen as an advantage for marketers that can be used to differentiate their products from the available competitors, giving the impression that their products are distinguishable, and thus creating more demand and generating increased intention to purchase more green products. Originality/value: The empirical results of this study address the gap in the prevailing body of literature in reference to the impact of green brand positioning and consumer attitude toward green brands, as well as the effect of green brand knowledge on green product purchase intention. This study found that green brand knowledge does not moderate the relationship between green brand positioning and green product purchase intention, thus providing insight into this subject matter, which has not been clearly examined in previous studies.